An introduction to counselling - McLeod, John. (Philadelphia : Open University Press, 2003)
Offers a comprehensive introduction to the theory and practice of counselling and therapy. This book covers various core approaches to counselling, and takes a critical, questioning approach to issues of professional practise. It also introduces a range of contemporary approaches, including narrative therapy, systemic, feminist and multicultural
Includes bibliographical references and index.
Keywords: Counseling